Combination of ipratropium bromide and salbutamol in children and adolescents with asthma: A meta-analysis - Xu, Hongzhen; Tong, Lin; Gao, Peng; Hu, Yan; Wang, Huijuan; Chen, Zhimin; Fang, Luo (PLOS ONE, 2021)
Background A combination of ipratropium bromide (IB) and salbutamol is commonly used to treat asthma in children and adolescents; however, there has been a lack of consistency in its usage in clinical practice. Objective To evaluate the efficacy and safety of IB + salbutamol in the treatment of asthma in children and adolescents. Methods The MEDLINE, Embase, and Cochrane Library as well as other Chinese biomedical databases (including China Biological Medicine Database, Chinese National Knowledge Infrastructure, Chongqing VIP, and Wanfang Chinese language bibliographic database) were systematically searched from the earliest record date to September 2020 for randomized controlled trials in children and adolescents (≤18 years) with asthma who received IB + salbutamol or salbutamol alone. The primary outcomes included hospital admission and adverse events. A random effects model with a 95% confidence interval (CI) was used. Subgroup analysis was performed according to age, severity of asthma, and co-interventions with other asthma controllers. This study was registered with PROSPERO. Results Of the 1061 studies that were identified, 55 met the inclusion criteria and involved 6396 participants. IB + salbutamol significantly reduced the risk of hospital admission compared with salbutamol alone (risk ratio [RR] 0.79; 95% CI 0.66–0.95; p = 0.01; I2 = 40%). Subgroup analysis only showed significant difference in the risk of hospital admission in participants with severe asthma exacerbation (RR 0.73; 95% CI 0.60–0.88; p = 0.0009; I2 = 4%) and moderate-to-severe exacerbation (RR 0.69; 95% CI 0.50–0.96; p = 0.03; I2 = 3%). There were no significant differences in the risk of adverse events between IB + salbutamol group and salbutamol alone group (RR 1.77; 95% CI 0.63–4.98). Conclusion IB + salbutamol may be more effective than salbutamol alone for the treatment of asthma in children and adolescents, especially in those with severe and moderate to severe asthma exacerbation. The very low to high quality of evidence indicated that future well-designed double-blind RCTs with large sample are needed for research on evaluating the effectiveness of IB + salbutamol treatment for asthma in children and adolescents.